A Comparative Study of Investments in Tourism, Health, Education, and Mining and its impact on Poverty Alleviation in West Nusa Tenggara - Supiandi, Supiandi; Pramuja, Risky Angga; Masud, Riduan; Nahar, Faiza Husnayeni; Azizurrohman, Muhammad (Advances in Tourism Studies, 2023)
West Nusa Tenggara is one of the provinces in Indonesia that has been struggling with poverty for a long time. Over the years, the government and private sector have invested heavily in various sectors to improve the economic condition of the province. This paper compares the impact of investments in tourism, health, education, and mining on poverty alleviation in West Nusa Tenggara. The study used both qualitative method to analyze the data collected through surveys and interviews. The results indicate that investment in tourism and education has a more significant impact on poverty alleviation compared to investments in health and mining. The paper concludes by highlighting the need for the government and private sector to focus more on sustainable investments in tourism and education to improve the economic condition of West Nusa Tenggara.